Uji Aktivitas Antikanker Ekstrak Etanol, Fraksi Polar, Semipolar, dan Nonpolar Herba Kitolod (Isotoma longiflora (L) C.Presl) terhadap Sel T47D - Selviana, Selviana; , Maryati, Ph.D., Apt (2016)
Kitolod herbs (Isotoma longiflora (L) C.Presl) predicted have anticancer activity. In the previous research, kitolod herbs have anticancer activity on WiDr and HeLa cells. This study aims to determine the cytotoxic activity of ethanol extracts, polar, semipolar and nonpolar fractions of kitolod herbs against breast cancer cells T47D and the chemical compounds contained in the samples. Samples was macerated by 96% ethanol. Fractionation performed by Vacum Liquid Chromatography method with G60 silica as stationary phase and as the mobile phase n-hexane: ethyl acetate (9:1, 8:2, 7:3, 6:4, 5:5) and ethanol 96%. The chmical compounds were identificatied by TLC method with n-hexane: ethyl acetate (7:3) as mobility phase and used reagents like dragendorf, anisaldehid, FeCl 3 , and sitoborat. Cytotoxic test performed on cancer cells T47D using MTT assay method. Cytotoxic test results showed that the ethanol extract, polar, semipolar, and nonpolar fractions of kitolod herbs have low cytotoxic activity to against T47D cells with IC 50 values respectively were 418,46; 665,74; 526,18; 856,12 µg/mL. The chemical compounds classes showed the ethanol extracts and polar fraction contains alkaloids, terpenoids, saponins, phenolic, tannins and flavonoids. The semipolar and nonpolar fractions contains similiar compounds with similiar to ethanol extract except alkaloids.